Penerapan AI Untuk Meningkatkan Kualitas Pendidikan Di SMP Negerti 3 Kota Sorong - Fitriyani Tella; Teguh Hidayat Iskandar Alam; Murni; Irman Amri (Abdimas: Papua Journal of Community Service, 2025)
The rapid advancement of digital technology has necessitated artificial intelligence (AI) literacy in the education sector. Unfortunately, the understanding of AI among teachers and students—particularly in underdeveloped regions like Sorong City—remains limited. This community service activity aimed to enhance participants’ comprehension, technical skills, and ethical awareness in AI utilization at SMP Negeri 3 Kota Sorong. The methods involved interactive lectures, hands-on training, group discussions, and formative evaluations through pre-tests and post-tests. The results demonstrated significant improvements in four key indicators: understanding of AI concepts, skills in using AI-based applications, digital ethics awareness, and interest in AI-related careers. The average participant scores increased by over 60%. The program successfully fostered a participatory and inclusive learning environment and cultivated interest in the educational use of technology. This training is recommended for broader implementation to accelerate digital literacy equity across educational institutions.